The in-hospital tuberculosis diagnostic cascade and early clinical outcomes among people living with HIV before and during the COVID-19 pandemic - a prospective multisite cohort study from Ghana. (March 2023) - Åhsberg, Johanna; Bjerrum, Stephanie; Ganu, Vincent Jessey; Kwashie, Augustine; Commey, Joseph Oliver; Adusi-Poku, Yaw; Puplampu, Peter; Andersen, Åse Bengård; Kenu, Ernest; Lartey, Margaret; Johansen, Isik Somuncu
Highlights: The gap in the access to tuberculosis testing was equally large over the pre-/COVID-19 periods. Less than half the severely ill admitted patients with HIV had an Xpert MTB/RIF result. The tuberculosis prevalence rate and 8-week all-cause mortality rate were unacceptably high. Missed or delayed tuberculosis diagnosis among people with HIV may be critical. Abstract : Objectives: The COVID-19 pandemic had a disruptive impact on tuberculosis (TB) and HIV services. We assessed the in-hospital TB diagnostic care among people with HIV (PWH) overall and before and during the pandemic. Methods: In this prospective study, adult PWH admitted at three hospitals in Ghana were recruited if they had a positive World Health Organization four-symptom screen or one or more World Health Organization danger signs or advanced HIV. We collected data on patient characteristics, TB assessment, and clinical outcomes after 8 weeks and used descriptive statistics and survival analysis. Results: We enrolled 248 PWH with a median clusters of differentiation 4 count of 80.5 cells/mm 3 (interquartile range 24-193). Of those, 246 (99.2%) patients had a positive World Health Organization four-symptom screen. Overall, 112 (45.2%) patients obtained a sputum Xpert result, 66 (46.5%) in the prepandemic and 46 (43.4%) in the pandemic period; P -value = 0.629. The TB prevalence of 46/246 (18.7%) was similar in the prepandemic 28/140 (20.0%) and pandemic 18/106 (17.0%) population; P -value = 0.548. The 8-week all-cause mortality was 62/246 (25.2%), with no difference in cumulative survival when stratifying for the pandemic period; log-rank P -value = 0.412. Conclusion: The study highlighted a large gap in the access to TB investigation and high early mortality among hospitalized PWH, irrespective of the COVID-19 pandemic.